Smoking behavior among third year dental students in Latin American countries: prevalence, perceptions, and risk factors - Irene Tamí-Maury; María Guadalupe Silva-Vetri; Maytté Marcano-Caldera; Alessandra Baasch; Alexander V Prokhorov (Instituto Nacional de Salud Pública, 2017)
Objective. To examine the association between tobacco-related risk factors and smoking among third-year dental students in Latin American countries. Materials and methods. Logistic regression models were used to analyze Global Health Professions Student Survey (GHPSS) data. Results. Of 5 605 respondents, 33% smoked and 45% had been exposed to secondhand smoke during the previous month, 34% smoked in school buildings during the past year, and 85% had never received formal training in smoking cessation. Smoking was significantly associated with male sex; Bolivian, Chilean, or Mexican nationality; exposure to secondhand smoke; lacking self-perception of being a "role model" for patients; and not believing that health professionals who smoke are less likely to advise patients to quit smoking. Conclusions. All dental schools should encourage tobacco-free policies and offer cessation services. Cessation training must be incorporated into dental curricula to include dental professionals in the battle against the tobacco epidemic.